PUBLIC MANAGEMENT OF MUNICIPAL SOLID WASTE IN THE GRANDE ABC REGION (Gestão & Regionalidade, 2015)
This article presents the results of a descriptive survey in the Grande ABC region. It is justified by the government's liability for the management of Municipal solid waste (MSW), especially from the Law no. 12.305/2010, the National Policy on Solid Waste. This study aimed to describe and compare MSW management practices adopted by the seven municipalities in this region. Seventeen interviews with members of the government and cooperatives involved in waste management were carried out. Data were analyzed by content analysis. The conclusion was that the selective collection walks at a slow pace in most municipalities regarding the implementation and institutionalization. Representatives of the unions stated that the dependence of the government and its changes interfere directly with the performance of selective collection, because they need to adapt to every change of government, which can cause discontinuities or downtime.